Design and Construction of Mini Single Turbine PLTU Demonstration Equipment: As a Thermodynamics Learning Media - K, Arwizet; Leni, Desmarita; Lapisa, Remon; Kusuma, Yuda Perdana; Anugrah, Pinto (IJIS Edu : Indonesian Journal of Integrated Science Education, 2024)
Thermodynamics is often considered difficult for students to grasp because it involves abstract concepts that are challenging to visualize without visual aids or physical demonstrations. This research involves the design of a mini power plant trainer as a teaching tool to visualize basic thermodynamics concepts, such as heat transfer, conversion of heat energy into mechanical energy, phase change from steam to liquid, and thermal efficiency. The trainer is designed according to the requirements of the system provided by the thermodynamics lecturer at the State University of Padang, taking into consideration the teaching material and safety aspects. The power plant trainer consists of four main components, including a boiler with a 15-liter water capacity equipped with an automatic sensor stove that can shut off when it reaches 4 bars of pressure and restarts when it drops below 4 bars, a single propeller turbine, a 12-volt generator, and a vertical condenser with coolant flow in the same direction as the steam flow. The testing results of the trainer yielded a boiler efficiency of 46%, thermal efficiency of 21%, with the steam power generated by the boiler at approximately 1734 Watts, condenser power at 1478 Watts, cooling power to convert wet steam into liquid at 119 Watts, and turbine power at 375 Watts. The maximum electrical power reached 2.94 Watts with a voltage of 12 volts and a current of 0.21 amperes. It took 31 minutes to heat 15 liters of water in the boiler to steam with a temperature of 146°C and a pressure of 58 Psi. The trainer can be operated (can rotate the generator) for 4 minutes until the steam pressure drops to 20 Psi. Based on the testing results, the trainer can be operated smoothly and is capable of illustrating difficult thermodynamics concepts that are hard to visualize. Therefore, in an effort to enhance the quality of learning, this trainer can be used as a simulation tool for thermodynamics education.